Exploring Identity Crisis in Chitra Banerjee Divakaruni’s Mistress of Spices - Bhardwaj, Devya (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Chitra Banerjee Divakaruni’s The Mistress of Spices is an exceptional novel that delves into the mystical powers of spices. The protagonist, Tilo, serves as the Mistress of Spices, using their magical properties to address the various issues faced by her customers who visit her shop. Tilo sees herself as the keeper of this secret power, embodying multiple identities throughout the story. The novel intricately portrays the struggles related to cultural identity. Through Tilo’s character, Divakaruni authentically examines the challenges of identity crisis, presenting it with depth and nuance in this remarkable narrative.